Türk borçlar hukukunda ikale sözleşmesi - Armağan, Davut (İstanbul Medipol Üniversitesi, Sosyal Bilimler Enstitüsü, 2022)
İkale sözleşmesi geniş anlamda borç ilişkisini sona erdiren hallerden biridir. Türk Borçlar Kanunu'nda düzenlenmemiş olan bu sözleşmenin dayanağını sözleşme özgürlüğü prensibi oluşturmaktadır. Tarafların aralarındaki borç ilişkisinin devamını arzu etmediği hallerde bu borç ilişkisini karşılıklı olarak anlaşmak suretiyle sona erdirmeye imkân vermektedir. Çalışmada ikale sözleşmesi borçlar hukuku bakımından incelenmiştir. Bu kapsamda çalışma beş bölümden teşekkül etmiştir. İlk bölümde, ikale sözleşmesinin tanımı, hukuki niteliği, türleri ve benzer kurumlarla mukayesesi ortaya konulmuştur. İkinci bölümde ikale sözleşmesinin konusu incelenmiş, üçüncü bölümde ise ikale sözleşmesinin kuruluşu, içeriği ve geçerliliği hususları ele alınmıştır. Dördüncü bölümde ise ikale sözleşmesinin hükümleri ele alınmış, son bölümde ise ikale sözleşmesi bakımından gündeme gelebilecek özel durumlar ortaya konulmuştur.

The termination contract is one of the situations that terminate the debt relationship. This contract, which is not regulated under the Turkish Code of Obligations, is based on the principle of freedom of contract. In cases where the parties do not wish to continue the debt relationship between them, it allows them to terminate this debt relationship by mutual agreement. In this study, the termination contract is analysed in terms of the law of obligations. In this context, the study consists of five chapters. In the first chapter, the definition, legal nature, types of the termination contract and its comparison with similar institutions are presented. In the second chapter, the subject of the termination contract is examined, and in the third chapter, the establishment, content and validity of the termination contract are discussed. In the fourth chapter, the provisions of the termination contract are discussed, and in the last chapter, special cases that may arise in terms of the termination contract are put forward.
Termination contract in Turkish law of obligations
Keywords: Borç I?lişkisi; I?kale Sözleşmesi; Sona Erme; Sözleşme; Sözleşme Özgürlüğü; Debt Relationship; Termination Contract; Termination; Contract; Freedom of Contract